Politics government and politics of the UK, government and politics of the USA and comparative politics - Lemieux, Simon; Hammal, Rowena; Fairclough, Paul; Bennett, Anthony J. (Hodder Education, 2021)
Packed with insight into contemporary issues and analysis of the latest developments in UK and US Politics, including the 2019 UK General Election and 2020 US election, this textbook is specially designed to help your students perform to the best of their abilities in the AQA Politics Paper 1 and Paper 2 exams. This Student Textbook: - Strengthens your students' understanding of comparative politics through dedicated comparative politics chapters and synoptic links throughout - Builds your students' confidence by highlighting key terms and connections between different topics in the specification - Develops your students' skills of analysis and evaluation through activities, debates and exam-style questions - Provides answer guidance for exam-style questions online at www.hoddereducation.co.uk.